Forgiveness Role Between Adverse Childhood Experience and Anxiety Among Persons Deprived of Liberty - Jay Conde Wong; Jemerson Dominguez (Journal of Health and Behavioral Science, 2026)
Introduction Anxiety prevalence among PDL is 40% to 100%, and unmanaged anxiety may lead to more severe psychological and health concerns. Aim This study examined the mediating role of forgiveness in the relationship between adverse childhood experiences (ACEs) and anxiety among PDL. Methods A cross-sectional non-experimental design was conducted among 376 PDL. Participants completed the ACEQ, Heartland Forgiveness Scale, and GAD-7. Data were analyzed using correlation, regression, and mediation analyses. Results ACEs were positively associated with anxiety (r = .43, p < .001) and negatively associated with forgiveness (r = -.16, p = .002), while forgiveness was negatively associated with anxiety (r = -.37, p < .001). Forgiveness partially mediated the relationship between ACEs and anxiety (β = 0.104, p = .004). Conclusion Forgiveness partially mediates the relationship between ACEs and anxiety; however, trauma-informed interventions remain necessary to address underlying childhood adversity and reduce anxiety among PDL.